Investigations into Phenolic and Alkaloid Constituents of Jatropha tanjorensis by LC-MS/MS and Evaluating its Bioactive Property - Arun, K.P.; Brindha, P. (Asian Journal of Chemistry, 2015)
Jatropha tanjorensis (Euphorbeacea) leaves are used as a food and for various herbal medicines in India and African countries. But only diminutive information is available on the secondary metabolites and their correlation with its traditional uses. Reversed-phase Liquid chromatography with C18 bonded silica gel coupled to ultraviolet (UV) detection and mass spectrometer encompass of quadrupole mass analyzer with time-of-flight mass detection (micrOTOF-QII) was standardized for the identification of semipolar compounds in the extract. Total ion chromatogram (TIC) was processed using Hystar 3.2 software tools. Compounds were assigned by comparing their mass signals with compounds already reported and MS/MS spectral MassBank libraries. With this approach several compounds not reported previously from Jatropha tanjorensis were identified. The methanolic extract from leaves of Jatropha tanjorensis (MEJT) contained a complex mixture of 20 flavonoids predominantly as glycosides, with few aglycones. Isorhamnetin-3-glucoside-4'-glucoside, delphinidin-3-O-2''-O-b-xylopyranosyl-b-glucopyranoside, 6-c-hexosyl-8-c-pentosyl apigenin, cyanidin-3,5-di-O-glucoside, 3',7-dimethoxy-3-hydroxyflavone and 2'',3'',4',5,6'',7-hexa-O-methylisovitexin were found in the methanolic extract of J. tanjorensis leaves. The core aglycones of these flavonoids were identified as apigenin, luteolin, isorhamnetin, quercetin and kaempferol. Few other bioactive molecules like rhein, benzamidine and derivative of ellagic acid were also identified. Apart from phenolic compounds few medicinally potent alkaloids like norharman, harmane, salsolinol and anabasine were also identified. To depict its biological activity against cancer cells, inhibition of proliferation assay (MTT) was performed on human skin carcinoma cells (A431) with an IC50 of 58.53 μg/mL. The methanolic extract from leaves of Jatropha tanjorensis has shown potent antimicrobial activity against various strains of bacteria with an MIC of 7.8 μg/mL. The methanolic extract from leaves of Jatropha tanjorensis was also evaluated for its anti-inflammatory activity through proteinase inhibition activity (IC50 166.2 μg/mL), inhibition of protein denaturation (IC50 165.4 μg/mL) and membrane stabilization (IC50 160.4 μg/mL). Antioxidant property was evaluated using reducing hydroxyl ion assay with an IC50 of 46.43 μg/mL. Results acquired prove the potent efficiency of selected plant against various disease conditions progresses to cancer. Present study also provide the necessary information on the chemical composition of Jatropha tanjorensis, thus suggesting yet another ‘‘authentication’’ in the identification of the selected plant.